A Historical Overview and Initiating Historiography of Islam in the Philippines - Ajid Thohir (International Journal of Nusantara Islam, 2015)
Understanding the history of Islam in the Southeast Asia will be more accurate through the geo-political and historical background perspective in particular. This assumption is based on Western Colonial influence in the past such as Spanish, Portuguese, Dutch, British, French, and United States that makes up the typology of Islamic culture in South East Asian region, which is strengthens the plurality of Islamic character. It also seems increasingly clear, especially for the Muslim communities in Philippine, who represented the community formed of Moro Islamic movement. Islamic culture in the Philippine is produced by the Spanish and the United States colonial policy which determines the fate and the treats of Muslims as a conquered state. This historical background results the emergence of a heroic character in Philippines Muslims that is different from the other Muslims community in South East Asia who are relatively considered quiet and peaceful. This paper will briefly explain the historiography of Islam in South East Asia region through involving cases of Muslims in the Philippine who will not found the plurality of character in the other country.